Bangladeshi Non-Government College Teachers under Threat of Maintaining Sustainable Livelihood in the Crisis of Pandemic: A Phenomenological Case Study (Teacher’s World: Journal of Education and Research, 2023)
In this time of pandemic, the teaching community is admirably and desperately trying to avoid the crisis ‘tragedy of not earning’ in order to preserve their livelihood. This article explored the non-government honours and master’s college teachers' livelihoods from different perspectives during the COVID-19 to answer the four research questions. Some reports published in the mass media were influenced by the background of the study. Newspapers and TV channel reports mention that teachers, especially non-government college teachers, in Bangladesh struggled a lot in the COVID-19 pandemic due to their salary irregularities and termination. These reports inspired researchers to conduct this study to explore the authentic condition of their livelihood. This study employs a theoretical framework from the DFID’s Sustainable Livelihood Approach in order to illustrate the livelihood condition of teachers. This study employs a qualitative research paradigm based on phenomenological case study methodology, with the theoretical framework providing guidelines for in-depth interviews. Eight teachers from the eight-division of Bangladesh were interviewed. Due to the COVID-19 crisis, interviews were conducted through mobile phones. An interpretative thematic analysis was applied in this study. The study results show that teachers are in poor financial, physical, social, natural, and human conditions, and COVID-19 has destroyed their normalcy of life by causing insecurity, instability, and precarity. They are compelled to struggle to meet their basic demands, concentrating on different income-generating tasks rather than conducting classes. The government should take the initiative to provide soft loans to teachers as an incentive to survive in these emergencies. But the government should find sustainable solutions for the betterment of these college teachers, such as nationalisation of the college teachers or including them in the Monthly Payment Order (MPO) list.Teacher’s World: Journal of Education and Research, Vol. 48(2), Dec 2022, p.27-40